IMPROVEMENT OF THE QUALITY OF EDUCATION AND GRADUATE FROM PRODI PENDIDIKAN TEKNIK MESIN FKIP - Sri Murwantini (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
Improving the quality of education and graduates of FKIP Prodi Pendidikan Teknik Mesin can not be separated from the new paradigm of education which includes 5 (five) pillars, namely quality, autonomy, accountability, accreditation, and evaluation. Implementation of the new paradigm concept is to give autonomy to higher education institutions in this case is Program Studi Pendidikan Teknik Mesin FKIP Unparfor academic missions of education, research, and community service. However, Program Studi Pendidikan Teknik Mesin FKIP Unparrequired to be accountable in terms of academic grades and performance managementso that the resulting quality as the impact of goal achievement and autonomy in the form of competency should be maintained through quality assurance both external (accreditation) and internal (self-evaluation). In academic terms, graduates of Program Studi Pendidikan Teknik Mesin FKIP Unparmust prepare for the challenges of education in the form of demands mastery of information technology and pedagogical skills in the scientific approach adopted in the 2013 curriculum for primary and secondary levels of education.